2020
DOI: 10.1021/acs.jmedchem.0c01620
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design of Melanocortin 4 Receptor Ligands Based on the SHU-9119-hMC4R Cocrystal Structure

Abstract: The melanocortin receptors (MC1R–MC5R) belong to class A G-protein-coupled receptors (GPCRs) and are known to have receptor-specific roles in normal and diseased states. Selectivity for MC4R is of particular interest due to its involvement in various metabolic disorders, including obesity, feeding regulation, and sexual dysfunctions. To further improve the potency and selectivity of MC4R (ant)­agonist peptide ligands, we designed and synthesized a series of cyclic peptides based on the recent crystal structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 32 publications
3
21
0
Order By: Relevance
“…In the case of the MC4 receptor, the reference compound SHU9119 exhibits subnanomolar affinity with IC 50 = 0.15 nM. This is consistent with a recent report by Martin et al who found for this compound Ki = 0.029 nM [ 30 ]. All our hybrid peptidomimetics display potent binding to MC4R.…”
Section: Resultssupporting
confidence: 89%
“…In the case of the MC4 receptor, the reference compound SHU9119 exhibits subnanomolar affinity with IC 50 = 0.15 nM. This is consistent with a recent report by Martin et al who found for this compound Ki = 0.029 nM [ 30 ]. All our hybrid peptidomimetics display potent binding to MC4R.…”
Section: Resultssupporting
confidence: 89%
“…Interestingly, SHU-9119 remained a full agonist at the hMC1R and hMC5R and had weak partial agonist activity at the hMC3R 28 . As this was reported in 1995, and other publications also documented the association between DNal(2’) 7 and MC3R/MC4R antagonism or weak partial agonism 31 , we sought to determine if the DNal(2’) 7 residue might be a general marker of MC3R/MC4R antagonism. If so, we might then have a diagnostic tool for peptide mischaracterization over history since this DNal(2’) 7 change was frequently included in many series of melanocortin peptides designed in a variety of labs and then characterized pharmacologically at the University of Arizona.…”
Section: Resultsmentioning
confidence: 88%
“…Given the prevalence of GPCR crystal structures over other MP classes, SBDD for GPCRs is the most advanced, with three small-molecule candidates from Sosei Heptares currently in clinical trials [36]. SBDD studies from the past 2 years (Table 2) demonstrate that solved crystal structures of GPCRs with ligands are enabling the design of more selective drugs with novel chemical structures [37][38][39]. When multiple active-state structures are available, as in the case of the β2-adrenergic receptor (β2AR), virtual screening can enable the design of sought-after agonists [40,41].…”
Section: Structure-based Drug Designmentioning
confidence: 99%